"Give Me a Break—English Is Not My First Language!": Experiences of Linguistically Diverse Student Teachers. Issue 1 (October 2016) - Eros, John
Today's K–12 music educators interact regularly with students from culturally diverse communities and backgrounds. Although research exists on culturally diverse students, there is comparatively little research on music teachers who do, themselves, represent diverse cultures. The purpose of this study was to investigate the experiences of three linguistically diverse music student teachers. The primary research question was the following: In what ways have the participants' linguistically diverse backgrounds affected their student teaching experiences? Data were collected through a questionnaire, a journal response, observation/postobservation notes, individual semistructured interviews, and a focus group interview. The participants discussed experiencing tensions between using their native languages and using English, although they felt that their own experiences as English Learners (ELs) provided them with a useful perspective in working with EL students and helped them to develop EL-based instructional modifications. The participants had also considered how their linguistic backgrounds would fit into their career plans.